2016
DOI: 10.1158/1535-7163.mct-15-0582
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Prevents Brain Metastases Formation in Lung Adenocarcinoma

Abstract: Patients with nonsquamous non-small cell lung cancer (nsNSCLC; largely lung adenocarcinoma) are at high risk of developing brain metastases. Preclinical data suggested that anti-VEGF-A therapy may prevent the formation of nsNSCLC brain metastases. Whether non-brain metastases are also prevented, and whether bevacizumab shows a brain metastasespreventive activity in cancer patients is unknown. Data of one nsNSCLC (stage IIIB/IV, AVAiL) and two breast cancer bevacizumab trials (HER2 negative, AVADO; HER2 positiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 33 publications
2
77
1
Order By: Relevance
“…In fact, targeting of VEGF with bevacizumab has been shown to reduce the incidence of brain metastasis in a mouse model of non-small-cell lung cancer (NSCLC), and when combined with carboplatin and paclitaxel, is associated with a reduced frequency of brain metastases as a site of first relapse in patients with this disease 42 . Similarly, treatment with an antibody targeting VEGF receptor 2 (VEGFR2) increased the efficacy of HER2-targeted therapies against established brain metastases from HER2-positive breast cancer in a mouse xenograft model 43 .…”
Section: The Abnormal Tumour Vasculaturementioning
confidence: 99%
“…In fact, targeting of VEGF with bevacizumab has been shown to reduce the incidence of brain metastasis in a mouse model of non-small-cell lung cancer (NSCLC), and when combined with carboplatin and paclitaxel, is associated with a reduced frequency of brain metastases as a site of first relapse in patients with this disease 42 . Similarly, treatment with an antibody targeting VEGF receptor 2 (VEGFR2) increased the efficacy of HER2-targeted therapies against established brain metastases from HER2-positive breast cancer in a mouse xenograft model 43 .…”
Section: The Abnormal Tumour Vasculaturementioning
confidence: 99%
“…In this study, a total of 112 BM events (defined as single cells, micrometastases and macrometastases), were observed in the eight control animals, while only two brain metastatic events occurred in the ten bevacizumab-treated mice (P<0.001) (20).…”
Section: Rational For Targeting Angiogenetic Pathways In Cns Metastasmentioning
confidence: 64%
“…Even though the studies are not comparable (in particular, PFS assessment was at the investigator's discretion in the EOLE study), median PFS was similar in both studies (6.7 months). A recent analysis of data from the AVAiL study went further and concluded that the BM rate as the first site of recurrence was significantly lower in the bevacizumab arm when compared to the control chemotherapy arm (2.6 vs. 5.8%; p = 0.01), with a lower risk of BM development over time (HR 0.36, p = 0.001) [22] . For the w/oBM patients analysed in the EOLE study, OS was shorter than for those reported in the BRAIN phase II study for wBM patients (16.0 months) [18] , possibly due to a greater diversity of patients and first-line chemotherapy combinations in the EOLE study.…”
Section: Discussionmentioning
confidence: 99%